SIRIH AS A SYMBOL OF VERBAL AND NON VERBAL MESSAGES IN ACEH COMMUNITIES - Rahmawati; Mawaddah, Mawaddah (IJRDO - Journal of Social Science and Humanities Research, 2020)
This present study seeks to examine communication based on “sirih” as the symbol related to the message contained verbally and non-verbally appears and develops in the city of Banda Aceh. The targets studied are the essence, function and meaning of the symbols contained in the message as communication media in the phenomenon of social and cultural life. This research employed a descriptive qualitative approach that is packaged in phenomenology. This approach, seeing that phenomena must be carried out and understood holistically, prioritizes process over outcome. Obtained results showed that “sirih” into a community tradition has reflected a variety of symbols from the messenger by ignoring the meaning of the recipient of the message, especially in the meaning of betel in various official ceremonies and in daily life as traditions and customary traditions that become the inculcation of values and norms carried out and trusted and believed can bring blessings in human life in social life, although not all people are able to understand and interpret the message contained therein.